Multi-wavelength brillouin fiber laser by utilizing fiber bragg grating
A ring cavity multi-wavelength Brillouin fiber laser by utilizing fiber Bragg grating is evolved to increase the transmission or data rate in the optical fiber communication especially in dense wavelength division multiplexing system. The combination of stimulated Brillouin scattering effect and fiber Bragg grating’s reflectivity enhances the multi-wavelength generation in order to transmit a lot of information at the same time. A ring cavity configuration has been experimental demonstrated with different single mode fiber lengths in which act as a Brillouin gain medium in stimulated Brillouin scattering effect. The amplified Brillouin pump power of 8 dBm to 18 dBm with a step increment of 1 dBm was applied in the laser system. Five different single mode fiber lengths of 8 km, 9 km, 10 km, 11 km and 12 km with nine output coupling ratios of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% and 90% were optimized to generate more output signals. Overall, the results showed that the investigation of Brillouin threshold power for first Brillouin Stokes signals was critically depends on the selective single mode fiber lengths and output coupling ratios. The lowest Brillouin threshold power of 8 dBm was achieved when 10%, 20%, 30% and 40% of the output coupling ratio at 10 km of single mode fiber was applied into the ring cavity while the highest Brillouin threshold power of 12 dBm was recorded by using 8 km of single mode fiber with 60%, 70%, 80% and 90% of output coupling ratios. Besides that, up to maximum 38 generated Brillouin Stokes signals with 16.00 dB of average optical signal to noise ratio value were recorded at 1550 nm of Brillouin pump wavelength when high amplified Brillouin pump power of 18 dBm was injected into the ring cavity. An optimum output coupling ratio of 90% and 10 km of single mode fiber were utilized in producing the multi-wavelength generation. The wavelength selectivity based on the Fiber Bragg Grating’s properties constrains the tuning range ability of this laser system. The multi-wavelength generation only occurred within 1544 nm to 1556 nm of Brillouin Pump wavelength according to the 3 dB bandwidth of 5 nm of the fiber Bragg grating. In short, the better performance of multi-wavelength Brillouin Fiber Laser by utilizing fiber Bragg grating was successfully demonstrated whereby the most multi-wavelength generation produced at 10 km of the effective Brillouin gain medium.